Does altruistic impact investment decision? evidence from Indonesia - Farah Amalia; Adellia Putriani; Liana Mangifera; Yohanes Suhardjo (Universitas Islam Negeri Walisongo Semarang, 2022)
Purpose - The purpose of this study was to examine the effect of altruistic and egoistic as behavioral variables on socially responsible investment decision. This paper also investigates the aspects that investors consider the most in making decisions.Method - A total of 108 sample respondents were selected using a purposive sampling technique. The criteria used are capital market study group students who have at least one ethical stock in their portfolio. Conjoint and regression analysis were involved to conduct the research.Result - The results showed that the investment attributes that investors prioritize are industry focus followed by return and risk. Furthermore, the most preferred industry focus is ‘sustainable asset’ followed by ‘no focus’ and ‘arms and defense’. Investment preferences in sustainable assets are based on the altruistic value of investors. Altruism has been shown to have a significant positive effect on investors' decisions to invest their funds in stock which belong to socially responsible investment. On the other hand, the egoistic value has a significant negative effect on the decision to invest in socially responsible investment.Implication - By looking at the research result, companies as stock issuers may consider to create or make their stock sustainable. This research would be beneficial for investment analysts or consultants in providing advice for their clients.Originality - This research uses altruistic and egoistic variables as psychological variables in investment decisions. In addition to using behavioral finance, it also involves value-belief-norm theory to explain the phenomena and discuss altruistic value in Islam perspective.